Can malnutrition predict mortality in heart failure with low ejection fraction? Implications for multidisciplinary care - Elisa Calisgan; Bayram Ozturk; Akyol, Betul; Kemal Gocer (Journal of the Pakistan Medical Association, 2025)
Objectives: To evaluate malnutrition’s predictive potential and significance with respect to overall mortality related to heart failure with low ejection fraction. Method: The cross-sectional, prospective study was conducted from June to August 2022 at the Kahramanmaras Sutcu Imam University and the Osmaniye Duzici State Hospital, Turkiye, and comprised heart failure patients with low ejection fraction. Malnutrition status was evaluated using the Global Leadership Initiative on Malnutrition criteria. The patients were divided into malnutrition group A and healthy group B. Prognostic nutritional index and controlling nutritional status scores were calculated and compared. All the patients were followed up either through telephone or clinic visits for up to one year. The number of hospitalisations and length of hospital stay within a year were recorded and compared. Data was analysed using SPSS 22. Results: Of the 216 patients with mean age 67.10±5.59 years, 110(50.9%) were males and 106(49.1%) were females. There were 57(26.4%) subjects in group A and 159(73.6%) in group B. Malnutrition, length of hospital stay and increased neutrophils were independent predictors of death (p<0.05). Conclusion: Malnutrition was found to be common among heart failure outpatients, and could significantly help identify those at increased mortality risk. Key Words: Malnutrition, Heart failure, Low ejection fraction, Mortality.